KALIMAT MINOR DALAM ACARA MATA NAJWA - Wiji Hastuti; Hasnah Faizah; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study entitled Minor sentence in the event of Mata Najwa. The purpose of research conducted by the author with the title of the study is a minor sentence describing the type of minor sentence used in the event Mata Najwa and also explain the meaning of a minor sentence. This type of research is qualitative descriptive method. The data source is the object of this study is Mata Najwa show on Metro TV. Data collected with a see-note technique and documentation of the five episodes during the month of September 2015 Mata Najwa events with different topics. The results showed there were 8 types of minor sentence, the sentence of minor calls, greeting, title, motto / slogan, the query expression, expression command, expression statements, and elliptical fragments, while the meaning of a minor sentence found in all kinds of minor sentence of the 69th Data with analyzed using contextual meaning. Meaning for unstructured minor sentence that is to be meaningful tribute, open conversation, politeness, notices, invitations, motivation, requests, orders, states, and other meanings, whereas for minor sentence structure to be meaningful affirmation, belief or truth.Key Words: a minor sentence , events , najwa eye.